Une ruée vers l’or contemporaine au Sahara: l’extractivisme aurifère informel au nord du Niger - Abdoulkader Afane; Laurent Gagnol (VertigO, 2021)
Since 2014 and the unexpected discovery of nuggets in the Saharan part of Niger, a feverish race towards the search for gold mobilizes tens of thousands of nomads, rural and urban, who have become gold diggers and come from Niger as well as from neighbouring or more distant countries. Sudden, massive and cosmopolitan, but also moving, sometimes violent and located in sparsely or uninhabited areas, gold mining is largely informal, i.e. often considered illegal but tolerated. Initially artisanal, it is becoming more and more mechanized, even industrial. The aim of this article is to analyse the spectacular development of gold mining in the north of Niger in order to draw up an initial provisional assessment six years after it began and, above all, to highlight the main challenges ahead. Our analysis is the result of several fact-finding missions in the field in 2018 and 2019, to meet the various players in this extractive rush. Contrary to the exploitation of other mining resources such as uranium, gold mining has the particularity of being very little monopolized by both multinational mining companies and the state, which is largely outmoded and cautious. Our approach will consider the rush as an exemplary case of setting up a complex, mobile and evolving system of resource predation exercised by multiple actors. We will address the transformations of informal and concerted regulation mechanisms between actors that took place during the different phases of the rush that we will qualify. If this rush produces major social, economic and political changes in a particularly unstable Saharan space, we will also discuss the disastrous and largely underestimated environmental and health effects. For this rush is symptomatic of what is happening on a wider scale and according to similar logics in the Sahara and the northern Sahel, where a vast pioneering nebula of gold exploitation has been spreading for the past ten years or so from the shores of the Red Sea to the Atlantic. More generally, the various features of the spectacular development of gold mining north of Niger that we will highlight make it a gold rush comparable in some respects and to some extent to the Californian model of the mid-nineteenth century. Without having too general an ambition to characterize the features common to any gold rush, we will nevertheless propose some avenues for reflection in this direction, distinguishing in particular three phases of gold rushes based on the case of the contemporary Nigerian Sahara.